Pola dan Strategi Komunikasi Dakwah Komunitas Project Dakwah di Kota Makassar - Fauziah Ramdani; Muh Ridwan (Bahasa Indonesia, 2025)
This study aims to describe the existence of the Project Dakwah community in Makassar city and its da'wah communication patterns and strategies. Using qualitative research methods with data collection techniques interviewing the founder of the community and the head of the akhawat (female) team. Library research was conducted with 30 types of reading material sources and direct observation of da'wah activities as well as publication of activities on social media. The results showed that the Project Dakwah community as one of the communities that emerged in 2019 until now has initiated the implementation of da'wah and humanitarian-based activities. Involving 60 people consisting of men and women as a management team and recruitment of volunteers based on da'wah events. The pattern and strategy of da'wah communication carried out by referring to surah An-Nahl verse 125, namely; namely Bil-hikmah, Mau'idzotul hasanah and Mujadalah billati iya ahsan. Da'wah bil hikmah is shown by the existence of a free attitude to make choices to be able to migrate and become a more pious person based on the level of each ability without coercion. Likewise Mau'idzotul Hasanah. Guiding gently so that they want to do better Mujadalah Billati Hiya Ahsan as an approach that prioritizes persuasive and assertive communication processes, encouraging the object of da'wah to think healthily and accept da'wah with gentle delivery without coercion. Using Burgoon's interaction adaptation theory which shows the desire of the Da'wah Project in line with the expectations and actions of the da'wah object by following a program that is flexible and adaptive to the conditions of the younger generation.